The Influence of Organizational Climate on Employee Performance PT. Sukses Mitra Sarana Duri, Bengkalis Regency - Lestari, Dwiana Indah; Saragih, Amansyah (Journal of Islamic Banking, Economics and Finance, 2026)
Organizational climate is a collection and pattern of environmental factors that determine the emergence of motivation and focus on reasonable or assessable perceptions, thus directly influencing the performance of organizational members. Observations and interviews with human resource development (HRD) revealed several problems, such as the lack of firmness from superiors in imposing sanctions on employees who violate Standard Operating Procedures (SOPs). The numerous rules and regulations that employees adhere to can lead to employee dissatisfaction with the conditions in the field. The purpose of this study was to determine the effect of organizational climate on employee performance at PT Sukses Mitra Sarana Duri, Bengkalis Regency. The population in this study was all 42 employees at PT Sukses Mitra Sarana Duri, Bengkalis Regency. The sampling technique used in this study was total sampling, a sampling technique used when the entire population is sampled. Thus, the sample size in this study was 42 people. The data analysis technique used was simple linear regression analysis. Based on the results of the research that has been conducted, it was concluded that the work climate (X) = with t count = 3.934> from t table 1.684 with a significance level of 0.000 less than 0.05. Therefore, Ho is rejected. and Ha is accepted, meaning that the work climate variable has a positive and significant effect on the performance of employees of PT Sukses Mitra Sarana Duri, Bengkalis Regency.